UPAYA UN WOMEN (UNITED NATIONS WOMEN) DALAM MEWUJUDKAN KESETARAAN GENDER DI INDIA - Welliswanti Sunardi; Muhammad Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study was conducted to explain the role of UN Women in its effort to achieve gender equality in India. This research was also conducted to find out the steps taken by UN Women in effort to realize gender in India. The theory used is the theory of International Organization by Clive Archer. The method used is qualitative. Most of the data collected through library research is collected from litearture studies, online data, and documents. The result of this research is that UN Women as an arena works well by holding a meeting on 16 Days of Activism against Gender-Based Violence in 2016 which can help India face problem related to gender discrimination, Enhancing Access to Justice for Women in Asia and the Pacific with several main agendas, one of which is to increase the capacity of women for the right to access justice and guarantee human rights. In its role as an actor, UN Women succeded in influencing the Indian government to issue the MGNREGA law which was implemented through the DWLAI program so that it could reach and empower Dalit women. UN Women as an instrument collaborates with Indian government through the SCE and Vocational Learning Programme which then produces several useful targets to help overcome gaps in the education sector. The conclusion of this study is that in the field of education, the role of UN Women as an arena, instrument, and independent actor has been running well. However, in the health sector, the role that is fulfilled is only the role of UN Women as an arena and lacks its role as an instrument and independent actor. Keywords:UN Women’s Role, Gender Equality, India.